Enriched electron donor sites and non-overlapping small polaron tunneling electrical conduction in oxygen-deficient β-Ga2O3 thin film on p-Si (100) - Karmakar, Subrata; Shiam, Istiaq Firoz; Droopad, Ravi; Haque, Ariful (Applied physics. A, Materials science & processing, 2024)
Monoclinic β-Ga 2 O 3 thin films were grown on heavily doped p-type Si substrate by pulsed laser deposition (PLD) at growth temperature 700 °C and oxygen partial pressure 1 × 10 –2 torr to determine its ac electrical behavior with frequency at different elevated temperatures for its possible harsh environment applications. X-ray diffraction (XRD) and X-ray photoelectron (XPS) spectra reveals a randomly orientated polycrystalline monoclinic β-Ga 2 O 3 phase with all possible chemical states of Ga and O. The electrical characteristics including impedance, dielectric and conductivity of β-Ga 2 O 3 /Si (100) heterostructures were performed by impedance analyzer in the frequency domain 100 Hz–1 MHz and temperature from 25 to 400 °C. Three different resistor–capacitor (RC) circuit in series were identified in the Nyquist plots (Z ʹʹ vs. Z ʹ ) which corresponds to the β-Ga 2 O 3 film, Si substrate and interfacial barrier effect and their contributions gradually compensating with temperature. The real electrical permittivity ( ε r ′ ) increases with temperature from ~ 5.35 (25 °C) to ~ 293.8 (400 °C) and exhibits a Maxwell–Wagner type electrical polarizations based on Koop’s phenomenological theory. The radius and contributions of Cole–Cole plots of dielectric diminished with temperature due to temperature dependent relaxation processes. The oxygen vacancies induced the enhanced electron donor sites in β-Ga 2 O 3 and the activation energy ( E a ) for ac electrical conduction for β-Ga 2 O 3 and Si was estimated to be ~ 0.87 eV and 0.07 eV, respectively. The variation of frequency exponents n 1 and n 2 with temperature revealed two different conduction mechanisms- (i) quantum mechanical model (QMT) for Si (100) substrate, and (ii) non-overlapping small polaron tunneling conduction model for β-Ga 2 O 3 . Graphical abstract